2022
DOI: 10.3390/agronomy12102377
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Spray Drift with Various Adjuvants in a Wind Tunnel

Abstract: When pesticides are sprayed, a significant portion of the droplets drifts away from the target. Using an adjuvant in spray liquid is an easy option for reducing droplet drift because there is no need to make any changes to the sprayer. The objective of the study was to determine the effects of seven commercially available adjuvants (Surfeco plus, Starguar, Kantor, Sterling, Control, Control WM, and Control DUO) with varying active ingredients on droplet size, surface tension, and viscosity. Since these propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Over the past few years, a vast amount of data has been stored and made available online, including dispersion modeling results and other air pollution-related information. Due to the sheer size of these datasets, it has become essential to devise tools capable of managing and deciphering them [20]. One such tool is the OpenAir package for R programming, which provides data and features useful for air quality estimation and other related research.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past few years, a vast amount of data has been stored and made available online, including dispersion modeling results and other air pollution-related information. Due to the sheer size of these datasets, it has become essential to devise tools capable of managing and deciphering them [20]. One such tool is the OpenAir package for R programming, which provides data and features useful for air quality estimation and other related research.…”
Section: Introductionmentioning
confidence: 99%
“…3). 23,24 Each spraying test was performed from a height of 50 cm. An axial fan on the exit side of the tunnel created artificial wind inside the tunnel (Fig.…”
Section: Wind Tunnelmentioning
confidence: 99%
“…Pesticide adjuvants can change the properties of the liquid, and provide new ideas for reducing spray drift [101]. Some researchers have found that the addition of methylated [102], mineral oil [103], non-ionic adjuvants [104], normaton [105], emulsion [106], and other adjuvants to the liquid can reduce the proportion of minor droplets that are easy to drift, improve the distribution of droplet diameter, and increase the amount of droplet deposition, which has a significant effect on the reduction in pesticide pollution.…”
Section: Plant Protection Uavsmentioning
confidence: 99%